Nekaj premislekov o prenovi osnovne šole in z njimi povezana stališča osnovnošolskih učiteljev - Breznikar Skočir, Nina (Sodobna pedagogika, 2024)
In the light of current school policy developments, this paper discusses two systemic solutions: in the first part, we raise the issue of the extended programme, which is seen as an integral part of the flexible-differentiation solutions in primary school, and in the second part, we discuss the solutions related to the National Knowledge Assesment (NKA). In the third part, we present the views of primary school teachers on these systemic solutions. The data on their views were obtained through qualitative research conducted within the Primary School Group of the Partnership for a Quality and Fair Education System, and collected through two rounds of focus group interviews in ten primary schools in Slovenia. As far as the extended programme is concerned, teachers stressed that it should be mainly in the function of relaxation, free time, non-directed activities. They oppose the „schoolisation“ of the extended programme. They point out that not all teachers are adequately formally educated to deliver the activities, and that in smaller schools it is difficult to provide a sufficient number of activities to provide pupils the opportunity to choose between them. Most teachers are highly critical of the solution concerning the national examination. They raise questions about the point of the national assessment, who it is actually for and what it is trying to achieve. Many feel that the NKA should have more systemic weight, or that we should ensure that pupils are encouraged to take part in it.
Keywords: compulsory education; education; extended programme; nacionalno preverjanje znanja; national knowledge assessment; osnovna šola; pedagogika; pedagogy; prenova; razširjeni program; reform; vzgoja in izobraževanje